Differences in Errors Between Students With Language and Reading Disabilities. (February 2017) - Avitia, Maria; Pagirsky, Matthew; Courville, Troy; DeBiase, Emily; Knupp, Tawnya; Ottone-Cross, Karen
Children with a specific learning disability in reading/writing (LDRW) and/or language impairment (LI) are likely to have difficulties across all areas of academic achievement, as a great deal of teaching and learning depends on intact reading skill and linguistic communication. Despite a large number of studies examining academic difficulties among these groups, there has been minimal research investigating types of errors made on tests of academic achievement. The present study compared academic error types of children with LDRW (Group 1) and children with LI (Group 3) to two distinct demographically matched control groups (Groups 2 and 4) using the Kaufman Test of Educational Achievement–Third Edition (KTEA-3) error analysis system. Findings indicate that children in the LDRW group or LI group, on average, made a greater number of errors than their matched counterparts. Statistically significant differences, with moderate effect sizes, were found between examinees in the clinical groups and their respective matched control groups across several error categories. Some of the largest differences were found in the Written Expression and Oral Expression subtests. Most importantly, the patterns of errors made by LDRW and LI samples differed notably on the various tasks, providing new insights about these clinical samples.